2018
DOI: 10.4172/2155-9880.1000573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hospital-based Cardiac Rehabilitation on Quality of Life and Physical Capacity in Acute Myocardial Infarction Patients: 2 Years Follow Up

Abstract: Objective: The aim of this study was to investigate the effect of hospital-based cardiac rehabilitation (CR) on quality of life (QOL) and physical functions in patients with acute myocardial infarction (AMI) during 2 years of followup.Methods: All AMI patients referred to the Cardiac Health and Rehabilitation Center (CHRC) were informed about CR and followed for 2 years on an outpatient basis from July 2010 to December 2015. Patients who were divided into a CR group and non-CR group. All patients took home-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…A study conducted by Kim et al, 2018 in Japan is consistent with our result, which showed that the mean score of the overall HRQL was 62.3 %, indicating a moderate level (Kim et al, 2018). The result of our finding is also consistent with a study conducted in South Korea (Kim and Hwang, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A study conducted by Kim et al, 2018 in Japan is consistent with our result, which showed that the mean score of the overall HRQL was 62.3 %, indicating a moderate level (Kim et al, 2018). The result of our finding is also consistent with a study conducted in South Korea (Kim and Hwang, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The study conducted by Mahmood et al reported that diabetes (DM), high blood pressure (HTN), hypercholesterolemia, smoking, drinking alcohol, obesity, and sedentary lifestyle as risk factors for MI (Mahmood et al, 2014). Other identified risk factors are unhealthy diet, lack of exercise, loneliness and social isolation (Kim et al, 2018). Because of illness manifestations following MI, the healthrelated quality of life (HRQL) could be harmed.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely a consequence of structural and/or functional changes to the heart as a result of the acute cardiac event and subsequent medical treatment, alongside inactivityrelated declines following the restriction of activity levels due to hospitalisation and recovery [2]. Improvements in physical capacity through CRF and muscular strength assist people to return to or exceed their level of functioning prior to their cardiac event [4]. In addition to improving physical capacity, cardiac rehabilitation aims to reduce the risk of subsequent cardiac events through an improvement in cardiac risk profile [1], and clinical trials have demonstrated that participation in supervised exercise training results in significant improvements in traditional cardiovascular risk factors [1].…”
Section: Introductionmentioning
confidence: 99%